2021
DOI: 10.3390/en14185867
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Generation Control of Multi-Source Interconnected Power System Using FOI-TD Controller

Abstract: Automatic Generation Control (AGC) delivers a high quality electrical energy to energy consumers using efficient and intelligent control systems ensuring nominal operating frequency and organized tie-line power deviation. Subsequently, for the AGC analysis of a two-area interconnected hydro-gas-thermal-wind generating unit, a novel Fractional Order Integral-Tilt Derivative (FOI-TD) controller is proposed that is fine-tuned by a powerful meta-heuristic optimization technique referred as Improved-Fitness Depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The PS must be extremely responsive to fluctuate in load disturbance and follow the predicted situation for all variables. Among the various performance indices used to assess the efficacy of PS, the Integral Time Square Error (ITSE) (Naidu et al, 2014;Hasanien and El-fergany, 2017;Morsali et al, 2018;Daraz et al, 2021;Elkasem et al, 2021;Liu et al, 2022) has been found to be well suited for parametric optimization based on the overshoot and time settling. Therefore, in this research study, the ITSE is deemed as the cost function to be minimized, and its representation in terms of a three-field network is as follows:…”
Section: Multi Resolution Pid Controllermentioning
confidence: 99%
“…The PS must be extremely responsive to fluctuate in load disturbance and follow the predicted situation for all variables. Among the various performance indices used to assess the efficacy of PS, the Integral Time Square Error (ITSE) (Naidu et al, 2014;Hasanien and El-fergany, 2017;Morsali et al, 2018;Daraz et al, 2021;Elkasem et al, 2021;Liu et al, 2022) has been found to be well suited for parametric optimization based on the overshoot and time settling. Therefore, in this research study, the ITSE is deemed as the cost function to be minimized, and its representation in terms of a three-field network is as follows:…”
Section: Multi Resolution Pid Controllermentioning
confidence: 99%
“…Teaching Learning Based Optimization Algorithm (TLBOA) outperformed conventional numerical methods by competently solving various complex optimization problems, including the Optimal Power Flow (OPF) problem for the minimization of dual objective functions [29]. FDO demonstrated its capability by favorably dealing with the multi-source Interconnected Power System (IPS) via the implementation of a prolific Automatic Generation Control (AGC) [30], [31]. Further, FDO has also been utilized for the optimization of various NOCPs, and the solutions generated were validated by comparative and statistical analysis [32].…”
Section: Introductionmentioning
confidence: 99%
“…In order to make the actual output infinitely close to the ideal output through the controller, the minimum variance control can achieve this purpose well. The control system occupies a very important position in the modern industrial production process (Daraz et al, 2022(Daraz et al, , 2021Ibraheem et al, 2020a,b;Abdul-Adheem et al, 2020a,b;Soliman et al, 2020;Gorripotu et al, 2021Gorripotu et al, , 2019Meghni et al, 2017Meghni et al, , 2018. In actual production, a production process may have thousands of control loops working together, and these loops contain various types of controllers (Mahdi et al, 2022;Sain et al, 2022;Fekik et al, 2022aFekik et al, ,b, 2021aFekik et al, ,b,c,d, 2020aAli et al, 2022Ali et al, , 2021aAcharyulu et al, 2021;Ajel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%